Tadpole of Leptopelis ragazzii (Boulenger, 1896), Shoa Forest Tree Frog (Anura, Arthroleptidae) - Tiutenko, Arthur; Zinenko, Oleksandr (Herpetozoa, 2019)
The tadpole of poorly studied Leptopelis ragazzii (Boulenger, 1896), a high-altitude tree frog species from the Ethiopian highlands, is described for the first time and compared with closely related sympatric species - L. gramineus (Boulenger, 1898) and L. vannutellii (Boulenger, 1898).
CRIS-Team Scopus Importer:2024-12-16
Keywords: Arthroleptidae; Ethiopia; Harenna forest; Larva; Leptopelis gramineus; Leptopelis vannutellii; Tadpole